Comparative Analysis of Mooring System Performance with Variations in 4,6, and 8 Point Configurations on Accommodation Work Barges - Alan Nurdiansyah; Arif Fadillah (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2026)
In the maritime industry, an effective mooring system is essential to ensure the stability and safety of offshore operations. A mooring system is a collection of equipment and techniques used to maintain the position and stability of a structure at sea or on an accommodation work barge. In practice, there are still various challenges and problems in the use of mooring systems on accommodation work barges. Factors such as weather conditions, sea depth, and the type of anchor used must be considered. This study will focus on analyzing the factors that affect the mooring system, analyzing the ship's RAO, and evaluating the weight of the anchor and tension wire. This study aims to produce recommendations for the best mooring system and configuration based on four types of seabed. The analysis was carried out using Ansys AQWA software and criteria set by ABS, DNV, and API. The factor that most influences the tension wire is the environmental load received by the ship (currents, waves, wind). Differences in environmental loads will also result in different tension values. In holding power analysis, mud seabeds produce the lowest holding power, while rock seabeds produce the highest holding power but are difficult to anchor. The 8 mooring system configuration is suitable for floating hotel operations because it has a good motion response, while 6 mooring is recommended for well intervention work because it is more efficient during the work process. The best anchor placement is located at 45° - 60° from the ship's centerline because it has an even load distribution.